Vicious circulation of water deficiency an water pollution - "CANCER" of the rivers in the north of China - Liankang, Yang; Yuntang, Pan; Yi, Yang (Sociedade & Natureza, 2005)
Vicious circulation of water deficiency an water pollution - "CANCER" of the rivers in the north of China